FORMATION OF AN ORGANIZATIONAL AND ECONOMIC MECHANISM FOR MANAGEMENT OF THE INNOVATIVE POTENTIAL OF LIGHT INDUSTRY ENTERPRISES IN A COMPETITIVE ENVIRONMENT - BERDYCHEVSKYI, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study explores the development trends of light industry enterprises within the modern economic space, emphasizing key factors influencing the efficiency of business operations and innovative activities. The research systematizes theoretical and practical aspects of economic potential formation and management, highlighting the role of strategic decision-making in enhancing enterprise competitiveness. Existing approaches to defining the essence, structure, and components of an enterprise’s economic potential are thoroughly analyzed. Special attention is given to the economic content of the potential management process as an integral part of the overall enterprise management system. The study identifies the fundamental elements of a comprehensive enterprise potential management system, emphasizing its interconnection with competitiveness, adaptability, and sustainable development strategies. The paper substantiates the elements of an innovative potential management system tailored to the specific needs of light industry enterprises. A conceptual framework is proposed for the development of a comprehensive system that ensures effective innovative potential management, fostering technological advancement and market adaptability. Furthermore, the research defines and specifies the key elements of the organizational and economic mechanism essential for managing innovative potential. These elements serve as the foundation for optimizing business processes, stimulating investment in innovation, and strengthening market positions in a highly dynamic environment. The study’s findings contribute to the theoretical and methodological foundations of enterprise economic potential management and offer practical recommendations for improving strategic decision-making processes in light industry enterprises. The proposed comprehensive approach provides insights into enhancing operational efficiency, ensuring sustainable growth, and fostering a competitive edge in the global market.